2019
DOI: 10.1063/1.5125215
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes during the switching transition of chalcogenide selector devices

Abstract: Ovonic threshold switches are a favored choice for chalcogenide-based amorphous (a-) GeSex selector devices used in cross-point arrays of nonvolatile memories. Previous models of their nonlinear high-field conduction proposed a largely electronic-only switching mechanism, within a fixed density of electronic states. Here, we use a density functional molecular-dynamics supercell calculation to show that the high-current excited state configuration of a-GeSex has structural changes such as additional Ge-Ge bonds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…For the Ge chain, an additional Ge atom joins the chain by forming bond with a Ge in the chain. Guo et al 49 and Clima et al also observed the formation of new Ge-Ge bonds and over-coordinated Ge under high field and thermal excitation in GeSe, respectively 45 . The lengthened Ge chain and the more connected network by the formation of overcoordinated Ge could eventually lead to conductive local paths.…”
Section: Resultsmentioning
confidence: 93%
“…For the Ge chain, an additional Ge atom joins the chain by forming bond with a Ge in the chain. Guo et al 49 and Clima et al also observed the formation of new Ge-Ge bonds and over-coordinated Ge under high field and thermal excitation in GeSe, respectively 45 . The lengthened Ge chain and the more connected network by the formation of overcoordinated Ge could eventually lead to conductive local paths.…”
Section: Resultsmentioning
confidence: 93%
“…The scientific interest to better understand OTS memory devices is currently directed in understanding the nature of the localized defect structures that contribute to the formation of the MG states. With the Ge–S‐ and Ge–Se‐based OTS memory devices, there is evidence to suggest that the Ge–Ge bonds form chain‐like structures, 148 and these could provide a conductive path. The nature of the defect configurations that populate the high‐resistance amorphous phase and lead to the MG states needs to be reliably ascertained to permit one to better understand how devices can withstand the repeated cycling of 10 8 or greater in the OTS memory devices.…”
Section: Broader Aspectsmentioning
confidence: 99%
“…5b-c. The trap states A, B, C and D in the a-GeSAs models are mainly found to be associated with structural motifs consisting of Ge-Ge bonds/chains 40,41,54,57 , while the trap state E of a-GeSAs 43 is different from the others, and is dominantly associated with As-As bonds/chains. As the major sources of these traps, Ge-Ge bonds/chains therefore play a crucial role in OTS behavior, and As/S atoms also contribute to these in-gap states from the PDOS.…”
mentioning
confidence: 94%
“…39 Nonetheless, owing to being surrounded by large numbers of Ge atoms (41.8% of the next-nearest neighbors, Fig. S19), Ge atoms could migrate and form Ge-Ge laments 40,41 triggered by high electric elds in the FF process 17,42,43 , leading to the delocalization of conduction state. Such paths dramatically increase the conductivity, resulting in a sharp increase in I off by more than 140 times in the following switching operations (Fig.…”
mentioning
confidence: 99%